The Effect of Using Suggestopedia Among Students’ Speaking Ability - Yuli Puji Astutik (English Language in Focus (ELIF), 2019)
Speaking is an important skill to communicate in the globalization era. We cannot deny the failure is caused by many problems. The success of the learning is involved in complex things, especially in the lecturer’s ability in learning and teaching. Such as the interesting material, the using of media, the learning approach and strategy, the classroom management, school environment, completely facilitation, and many other aspects. The objective of this research is to find out the effect of using suggestopedia to the students’ speaking ability. The group had taught by using suggestopedia. It had conducted a pre-testing them first, then gave them treatment using suggestopedia and the last conducted a post-test. The instrument was used oral performance test. The criteria of the performance test scoring were a fluency, accuracy, content, and pronunciation. According to the result of statistical calculation, it is obtained the value of (t-observation) is 8,387 and the value of “tc” (t-critical) from the df (31) on degree of significance of 0,05 % is 1.6955. Based on the finding of this study it can be concluded that using suggestopedia method in increasing students’ speaking ability is effective.